Risk Assessment at the Plate Production Unit of PT. INKA (Persero) - Monalisa Ma'rifat; Atiya Thifal Rofifa; Tri Martiana (Universitas Airlangga, 2021)
Introduction: The plate manufacturing production unit is one of the work units in PT. INKA (Persero), which involves the interaction between humans and machines in its activities, heavy equipment, and materials, all of which can cause possible hazard impacts that can impact the safety and health of workers. The purpose of this study is to conduct risk assessment on occupational safety and health aspects by identifying risks, assessing risks, identifying control efforts and assessing residual risk as a form of efforts to prevent occupational accidents and occupational diseases, using existing resources effectively and efficiently. Method: This research is a type of qualitative research, through interviews and observations, with cross-sectional studies and descriptive analysis. The interviewees for this study were K3LH management managers, steel managers, and machine operators in the plate production unit (PPL). The tools in this study werean interview guide, Job Safety Analysis (JSA) and Hazard Identification Risk Assessment Determining Control (HIRADC) using the AS / NZS 4360: 2004 Risk Management Worksheet Standard Risk Matrix. Results: From the research, it was found that there are 94 hazards for 11 different machines. Regarding the risk levels, there are 9 extreme risk levels, 46 high risk levels, 33 medium risk levels and 6 low risk levels. Conclusion: There are still 61 risks with medium risk level and 6 remaining risks with high risk level that still need control. Control efforts have been implemented by PT. INKA (Persero) in accordance with the hierarchy of control, such as the use of PPE and the provision of work SOPs. Keywords: hazard identification, risk management, risk assessment, risk control, residual risk